Pembelajaran Bahasa Arab Di Indonesia Pada Era Revolusi Teknologi Tak Terbatas (Strengths, Weaknesses, Opportunities, And Threats) - Syindi Oktaviani R. Tolinggi (Institut Agama Islam Negeri (IAIN) Metro, 2021)
Technology comes to facilitate all matters and needs. Still, on the one hand, this technological revolution does not always and forever provide positive opportunities, but can also pose a threat to several aspects, not least in learning Arabic. Therefore, the purpose of writing this type of library research article is to provide an overview of the challenges faced by Arabic, strengths, weaknesses, threats, and opportunities that can be realized through learning Arabic in this era of unlimited technological revolution, especially in universities that will produce human resources to compete and meet the challenges and demands of technological development and globalization in the Arabic language field. The results of writing this article are, learning Arabic in Indonesia in the era of the infinite technological revolution has many challenges and demands to experience innovation in its components, such as the direction and objectives of learning, curriculum, materials, methodologies used, media, forms and how to evaluate, as well as educators. Based on this technological revolution, the Arabic language can also realize great opportunities both for employment Arabic graduates and for the existence of Arabic itself. Although on the other hand, due to irresponsible elements, the development of technology towards the world of Arabic learning raises several threats and weaknesses that must be constantly addressed.